Prevalence of gestational choriocarcinoma in a parous population in ten years - Wahaibi, Fatma Al; Gowri, Vaidyanathan; Kharusi, Suad Al; Rawahi, Thuria Al (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Choriocarcinoma is a rare disease with varying incidence in different parts of the world. Asian, American Indian and Africans are quoted to be at a higher risk. There are no epidemiological data from Middle East and hence authors studied the prevalence of choriocarcinoma in Oman, a Middle East nation with a high parity. Methods: This is a retrospective, descriptive, observational study done at tertiary care hospital; Royal Hospital from Jan 2010 to Dec 2019. Since all women are referred to a single center from all over the country, authors believe all cases are included over ten years. Results: There were 22 patients and the prevalence were 1 in 36966 live births. The main presenting symptom was abnormal uterine bleeding and all were gestational type of choriocarcinoma. Median gravidity was 6 and median parity was 5. Almost 80 % received chemo as their risk scoring was more than 7 and one woman died. Conclusions: The prevalence of choriocarcinoma was much similar to Europe and USA though the median gravidity and parity was high. Clinical features were comparable to the literature and management protocols were as per international recommendations.